Assessment of the nursing care product (APROCENF): a reliability and construct validity study - Danielle Fabiana Cucolo; Márcia Galan Perroca
ABSTRACT Objectives: to verify the reliability and construct validity estimates of the "Assessment of nursing care product" scale (APROCENF) and its applicability. Methods: this validation study included a sample of 40 (inter-rater reliability) and 172 (construct validity) assessments performed by nurses at the end of the work shift at nine inpatient services of a teaching hospital in the Brazilian Southeast. The data were collected between February and September/2014 with interruptions. Cronbach's alpha and Spearman's correlation coefficients were calculated, as well as the intraclass correlation and the weighted kappa index (inter-rater reliability). Exploratory factor analysis was used with principal component extraction and varimax rotation (construct validity). Results: the internal consistency revealed an alpha coefficient of 0.85, item-item correlation ranging between 0.13 and 0.61 and item-total correlation between 0.43 and 0.69. Inter-rater equivalence was obtained and all items evidenced significant factor loadings. Conclusion: this research evidenced the reliability and construct validity of the scale to assess the nursing care product. Its application in nursing practice permits identifying improvements needed in the production process, contributing to management and care decisions.